Large-scale freestanding nanometer-thick graphite pellicles for mass production of nanodevices beyond 10 nm. Issue 35 (10th July 2015) - Kim, Seul-Gi; Shin, Dong-Wook; Kim, Taesung; Kim, Sooyoung; Lee, Jung Hun; Lee, Chang Gu; Yang, Cheol-Woong; Lee, Sungjoo; Cho, Sang Jin; Jeon, Hwan Chul; Kim, Mun Ja; Kim, Byung-Gook; et al.
Abstract : Freestanding nanometer-thick graphite film as a promising material for EUVL pellicle shows high thermal and chemical stability with excellent heat dissipation property. Abstract : Extreme ultraviolet lithography (EUVL) has received much attention in the semiconductor industry as a promising candidate to extend dimensional scaling beyond 10 nm. We present a new pellicle material, nanometer-thick graphite film (NGF), which shows an extreme ultraviolet (EUV) transmission of 92% at a thickness of 18 nm. The maximum temperature induced by laser irradiation ( λ = 800 nm) of 9.9 W cm −2 was 267 °C, due to the high thermal conductivity of the NGF. The freestanding NGF was found to be chemically stable during annealing at 500 °C in a hydrogen environment. A 50 × 50 mm large area freestanding NGF was fabricated using the wet and dry transfer (WaDT) method. The NGF can be used as an EUVL pellicle for the mass production of nanodevices beyond 10 nm.